2018
DOI: 10.1016/j.indcrop.2017.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical water extraction as an environmentally-friendly technique to recover bioactive compounds from traditional Serbian medicinal plants

Abstract: Subcritical water extraction (SWE) has become a popular green extraction technique for the isolation of different classes of compounds from natural matrices. Low price, safety and green character of water, good yields of target compounds and reduced energy consumption, make this technique favorable for potential industrial applications. The purpose of this study was to evaluate antioxidant, antimicrobial and cytotoxic activity of four medicinal plants traditionally used in folk medicine of Serbia. Black mulber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 55 publications
1
57
0
Order By: Relevance
“…With respect to the temperature, the best results were achieved for PLE 8 and 9 performed at 176 and 200°C, respectively. In general, solvents have higher capacity to solubilise compounds at higher temperatures enabling its liberation from the matrix due to the cell rupture of plant samples and the destruction of sample surface . The results also reported that lower ethanol percentage was associated with an improvement of EY.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…With respect to the temperature, the best results were achieved for PLE 8 and 9 performed at 176 and 200°C, respectively. In general, solvents have higher capacity to solubilise compounds at higher temperatures enabling its liberation from the matrix due to the cell rupture of plant samples and the destruction of sample surface . The results also reported that lower ethanol percentage was associated with an improvement of EY.…”
Section: Resultsmentioning
confidence: 92%
“…In general, solvents have higher capacity to solubilise compounds at higher temperatures enabling its liberation from the matrix due to the cell rupture of plant samples and the destruction of sample surface. 31,32 The results also reported that lower ethanol percentage was associated with an improvement of EY. This can be explained because although the use of dual solvent mixture can enhance the extraction efficiency, higher percentages of ethanol lead to a decrease in the EY.…”
Section: Comparison Of Extraction Techniquesmentioning
confidence: 88%
“…Subcritical water enhances also mass transfer and desorption kinetics, potentiating the dissociation of the compounds from their complexes with matrix constituents [19]. Recently, a number of papers describing SWE of bioactive compounds from plants have been published [11,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The identification and quantification of phenolic compounds were performed according to the method previously described by Nastić et al (2018). In brief, D. ecastaphyllum extracts (20 μL) were injected into the HPLC system (Shimadzu Corporation, Kyoto, Japan) equipped with an LC-20AD prominence pump, a DGU-20AS prominence degasser, a CTO-10AS VP column oven, a SIL-20A HT prominence autosampler, and an SPD-M20A photodiode array detector (PDA).…”
Section: Phenolic Compounds Determination By Hplc-pda Analysismentioning
confidence: 99%